Skeletal muscle oxidative capacity in patients with cystic fibrosis. Issue 5 (20th April 2015) - Erickson, Melissa L.; Seigler, Nichole; McKie, Kathleen T.; McCully, Kevin K.; Harris, Ryan A.
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Do patients with cystic fibrosis have reduced skeletal muscle oxidative capacity, measured with near‐infrared spectroscopy, compared with demographically matched control subjects? What is the main finding and is its importance? Patients with cystic fibrosis have impairments in skeletal muscle oxidative capacity. This reduced skeletal muscle oxidative capacity not only appears to be accelerated by age, but it may also contribute to exercise intolerance in patients with cystic fibrosis. Exercise intolerance predicts mortality in patients with cystic fibrosis (CF); however, the mechanisms have yet to be elucidated fully. Using near‐infrared spectroscopy, in this study we compared skeletal muscle oxidative capacity in patients with CF versus healthy control subjects. Thirteen patients and 16 demographically matched control subjects participated in this study. Near‐infrared spectroscopy was used to measure the recovery rate of oxygen consumption (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz1g5cw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> mus V̇O2max</alternatives>) of the vastus lateralis muscle after 15 s of electrical stimulation (4 Hz) and subsequent repeated transient arterial occlusions. The <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz1g5gf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> mus V̇O2max</alternatives> was reduced in patients with CF (1.82 ± 0.4 min−1) compared with control subjects (2.13 ± 0.5 min−1, P = 0.04). A significant inverse relationship between age and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz1g5hz" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> mus V̇O2max</alternatives> was observed in patients with CF (r = −0.676, P = 0.011) but not in control subjects (r = −0.291, P = 0.274). Patients with CF exhibit a reduction in skeletal muscle oxidative capacity compared with control subjects. It appears that the reduced skeletal muscle oxidative capacity is accelerated by age and could probably contribute to exercise intolerance in patients with CF.